Discrepancy in the evaluation of explicit and implicit nutrition care outcomes for patients at risk of malnutrition: A qualitative study. Issue 3 (8th September 2021) - Al‐Adili, Lina; Orrevall, Ylva; McGreevy, Jenny; Nydahl, Margaretha; Boström, Anne‐Marie; Lövestam, Elin
Abstract: Background: Nutrition care plays a significant role in the prevention and treatment of malnutrition, although the challenge to establish the precise impact of a nutrition intervention on patient outcomes remains. Malnutrition can be associated with diverse underlying diseases and an increased risk of complications, which increases the difficulty of monitoring and evaluating the nutrition intervention. The aim is to gain an understanding of dietitians' reflections concerning nutrition care outcomes of interventions in patients at risk of malnutrition. Methods: Six semi‐structured audio‐recorded focus group discussions with registered dietitians from primary healthcare and hospitals ( n = 29) in Sweden were held at the dietitians' place of work or at the University. Focus group transcripts were analysed thematically to reveal patterns in the data and identify themes and subthemes. Results: The dietitians described an approach to nutrition monitoring and evaluation of patients at risk of malnutrition that was categorised into three themes: (i) quantitative explicit outcomes, based on objective measures and described as rigorous; (ii) quantitative estimated outcomes, based on estimates and described as less rigorous and (iii) qualitative implicit outcomes, based on patients' subjective perceptions and experiences of their health and described as difficult to measure. Conclusions: Findings indicate the need for new strategies to promote systematic and comprehensive nutrition monitoring and evaluation. Highlights: Dietitians endeavour to quantify and measure rigorous outcomes to enable nutrition monitoring and evaluation of patients at risk of malnutrition. The detitians described qualitative outcomes as those often being most significant to patients. Qualitative outcomes were described to be less well documented in the electronic health record and therefore implicit in nutrition monitoring and evaluation.